2019
DOI: 10.1039/c9tc02422k
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-controlled and solvent-dependent strategies for the synthesis of multicolor carbon dots for pH sensing and cell imaging

Abstract: Solvent-controlled, pH-dependent and solvent-dependent strategies are proposed to obtain multicolor carbon dots using the same precursor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 59 publications
2
54
0
Order By: Relevance
“…From the characterization studies, the fluorescent C-Dots emitted colourful emission such as blue (2.82 eV), green (2.59 eV), yellow (2.28 eV) and red (2.14 eV) light under different concentration of the solvent of DMF/H 2 O (2:1 vol/vol), EtOH/ CH 3 COOH (450:1 vol/vol), pure EtOH and pure DMF with increasing yield (50,70,87 and 90% Some research groups have found that differentiating the composition of reaction solvents is efficient in controlling CD bandages and thus modulating multicolored emitting CDs or long wavelength-emissive CDs. The CDs could be directly synthesized using different solvents from the same precursor or may be synthesized CDs dispersed in different solvents to observe the tunable property (Song et al, 2019)- (Bai et al, 2019;Jing et al, 2019). For example, Tian et al (2017) prepared all colour emitting CD using citric acid, urea as raw materials and three different solvents (water, glycerol, and dimethyl formamide) via a solvothermal method.…”
Section: Effect Of Solventmentioning
confidence: 99%
“…From the characterization studies, the fluorescent C-Dots emitted colourful emission such as blue (2.82 eV), green (2.59 eV), yellow (2.28 eV) and red (2.14 eV) light under different concentration of the solvent of DMF/H 2 O (2:1 vol/vol), EtOH/ CH 3 COOH (450:1 vol/vol), pure EtOH and pure DMF with increasing yield (50,70,87 and 90% Some research groups have found that differentiating the composition of reaction solvents is efficient in controlling CD bandages and thus modulating multicolored emitting CDs or long wavelength-emissive CDs. The CDs could be directly synthesized using different solvents from the same precursor or may be synthesized CDs dispersed in different solvents to observe the tunable property (Song et al, 2019)- (Bai et al, 2019;Jing et al, 2019). For example, Tian et al (2017) prepared all colour emitting CD using citric acid, urea as raw materials and three different solvents (water, glycerol, and dimethyl formamide) via a solvothermal method.…”
Section: Effect Of Solventmentioning
confidence: 99%
“…[14][15][16][17] Several synthetic strategies have been employed by different research groups for the synthesis of carbon dots with different colour emission. [18][19][20] Lei and coworkers reported an external heating free synthetic procedure for the fabrication of carbon dots using citric acid as the carbon source and 1-ethyl-3-(3-dimethylaminopropyl) carbodiimidehydrochloride (EDC) as the cross linking agent. [21] Control of reaction condition and passivation of surface of the carbon dots are the most frequently adopted strategies for the tuning of the fluorescence of carbon dots.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, the I D / I G ratios are widely used to evaluate the quality of carbon materials [ 19 ]. The ratio of I D / I G is about 0.63, indicating a high graphitization degree in Car-CDs [ 20 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%